Chiral phosphoric acid catalyzed aminative dearomatization of α-naphthols/Michael addition sequence - Zi-Lei Xia (Nature Portfolio, 2019)
Catalytic asymmetric dearomatization (CADA) reactions readily convert common aromatic compounds to diverse 3D chiral, polycyclic molecules. Here, the authors report an intermolecular asymmetric dearomatization of nucleophile-tethered α-naphthols affording functionalized cyclic ketones with high enantioselectivity.